Dose-dependent risk of neutropenia after 7-day courses of artesunate monotherapy in Cambodian patients with acute Plasmodium falciparum malaria. - Bethell, D; Se, Y; Lon, C; Socheat, D; Saunders, D; Teja-Isavadharm, P; Khemawoot, P; Darapiseth, S; Lin, J; Sriwichai, S; Kuntawungin, W; Surasri, S; et al. (2010)
BACKGROUND: Fears of emerging artemisinin resistance in western Cambodia have prompted a series of clinical trials investigating whether slow responses to antimalarial treatment can be overcome by increasing doses of drug. METHODS: Patients with uncomplicated malaria were allocated 1 of 3 oral artesunate monotherapy regimens (2, 4, or 6 mg/kg/day for 7 days) and were observed for 42 days. A series of safety measures, including complete blood count on days 0, 3, 6, and 14, was implemented because of a lack of safety data for these experimental doses. RESULTS: After 3 doses, geometric mean absolute neutrophil counts were reduced in all groups, and 2 patients required artesunate to be discontinued because of neutropenia (absolute neutrophil count, <1.0 × 10(3) cells/μL). Recipients of the 6 mg/kg/day dosage had significantly lower geometric mean absolute neutrophil counts than did recipients of the 2 and 4 mg/kg/day dosages at 6 and 14 days (P < .001 for each). Overall, 5 (19%) of 26 patients who received the 6 mg/kg/day dosage became neutropenic within 14 days, triggering a cohort-halting rule and ending the trial early. Pharmacokinetic data from neutropenic patients showed wide variance, with plasma clearance occurring significantly slower in neutropenic patients than in nonneutropenic patients. CONCLUSIONS: Artesunate remains a crucial drug for the treatment of malaria, and determining optimal dosing regimens is vital to overcome emerging resistant parasite strains along the Thai-Cambodian border. However, future experimental dosing studies must be designed with care, because the safety of such regimens can no longer be assumed. The artemisinin derivatives remain one of the safest classes of antimalarial drugs, but this study demonstrates that the dosing limit may have been reached.